2022
DOI: 10.1002/2475-8876.12269
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of LCZ categories and standards considering super high‐rise buildings suited for Asian cities based on the analysis of urban morphological properties of Tokyo

Abstract: The Local Climate Zone (LCZ) scheme is an urban classification system which classifies urban areas into discrete local climates by morphological and land cover characteristics, proposed based on urban heat island researches in 1970s to 2000s. However, while the original scheme defines high‐rise buildings as areas higher than 25 m on average, buildings over 100 m have become more common in Asia since the 2000s. With the heterogeneity of urban areas, directly applying the original LCZ scheme to Asian cities has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The methodology for LCZ mapping can be broadly categorized into two distinct approaches: the GIS-based method and the satellite image-based method [62], [63], [64]. The GISbased method generated LCZ maps based on calculated physical properties, including average building height, building coverage ratio, pervious surface fraction, and others [20], [62]. The satellite image-based method employs training samples of each LCZ type and supervised classification algorithms to generate LCZ maps for study areas [21], [29].…”
Section: A Lcz Map Of the Bth Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodology for LCZ mapping can be broadly categorized into two distinct approaches: the GIS-based method and the satellite image-based method [62], [63], [64]. The GISbased method generated LCZ maps based on calculated physical properties, including average building height, building coverage ratio, pervious surface fraction, and others [20], [62]. The satellite image-based method employs training samples of each LCZ type and supervised classification algorithms to generate LCZ maps for study areas [21], [29].…”
Section: A Lcz Map Of the Bth Regionmentioning
confidence: 99%
“…However, the effectiveness of GIS-based method relies on the availability of high-quality GIS data, which is often difficult to obtain [62], [66]. Moreover, some studies have pointed out that the LCZ factors ranges recommended by Stewart and Oke cannot match some LCZ types in Asian cities [20], [21], [29]. For the BTH Region in Asia, there are still challenges in determining the appropriate factors ranges for each LCZ type.…”
Section: A Lcz Map Of the Bth Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tokyo Metropolitan Area is also subject to increases in heat stroke incidence rates 2 and accommodates a society which is aging rapidly 15 . Furthermore, a limited number of studies have specifically investigated the relationship between building height and density and UHI intensity in the Tokyo Metropolitan Area 16 . Nor have the implications for urban heat mitigation been extensively considered.…”
Section: Introductionmentioning
confidence: 99%
“…15 Furthermore, a limited number of studies have specifically investigated the relationship between building height and density and UHI intensity in the Tokyo Metropolitan Area. 16 Nor have the implications for urban heat mitigation been extensively considered. Adopting the wet bulb globe temperature, Wang, Gao, Zhou, Kammen, & Peng 17 found that higher-rise and medium density buildings have comparatively lower heat stress levels in the Tokyo Metropolitan Area.…”
Section: Introductionmentioning
confidence: 99%